Impact of implementation interventions to improve substance use service delivery on recidivism among justice-involved youth - Angela A. Robertson; Sheena Gardner; Richard Dembo; Michael Dennis; Jennifer Pankow; Khirsten J. Wilson (Health & Justice, 2023)
Abstract Substance use disorders (SUD) are prevalent among justice-involved youth (JIY) and are a robust predictor of re-offending. Only a fraction of JIY with substance use problems receive treatment. This paper describes the impacts of system-level efforts to improve identification and referral to treatment on recidivism of JIY. A cluster randomized trial involving 20 county juvenile justice agency sites across 5 states was used to implement an organizational intervention (Core vs Enhanced) to juvenile justice staff and community-based treatment providers, working with 18,698 JIY from March 2014 to August 2017. Recidivism rates over four study time periods were examined. Logistic regression was used to predict recidivism as a function of site, need for SUD services, level of supervision, time, organizational intervention, and time x intervention interaction terms. Results indicated that Enhanced sites showed decreased levels of recidivism compared to Core-only sites, where it increased over time. Additionally, need for SU services, level of supervision, and site were significant predictors of reoffending. Findings suggest the potential value of facilitation of juvenile justice agency efforts to increasing identification of and referral to SUD services of JIY in need of such services for reducing further contact with the legal system.